Experimental Investigation on Metallurgical Properties on Effect of Dual Hybridization by Ultrasonic and Electric Energy in Friction Stir Welding for Joining Inconel 625 to Stainless Steel 304 - Sengupta, Kaushik; Mondal, Arpan Kumar; Bose, Dipankar; Chowdhury, Ivy (Transactions of the Indian Institute of Metals, 2024)
Utilization of Dual Hybridization of Ultrasonic and Electric Assistance together in Friction Stir Welding (FSW) method was experimented and comparative study had been made in the present paper for joining of two dissimilar high strength materials, ASTM A240 Grade 304 Stainless Steel and Inconel 625. Three different FSW processes have been adopted for the present study which includes Ultrasonic-Assisted FSW (UAFSW), Electric-Assisted FSW (EAFSW) and Dual Ultrasonic & Electrically Assisted FSW (DUEAFSW), at similar process parameters, and a comparative study to understand the effect of the electric current and ultrasonic energy on FSW process has been made. For dual hybridization of ultrasonic assistance to EAFSW process, an ultrasonic transducer of 20 kHz is used along with similar process parameters for FSW and EAFSW for understanding the effect on addition of the dual hybridization on FSW at joint properties including joint efficacy, elongation, hardness, thermal profile and microstructure which has been studied and compared to analyze improvement with variation in process parameters and suitable process parameters advised for industrial use of the hybrid technology.